PERBANDINGAN USIA KRONOLOGIS BERDASARKAN GAMBARAN RADIOGRAFIS DARI TAHAP ERUPSI GIGI MOLAR KETIGA RAHANG BAWAH DENGAN METODE OLZE ANTARA PASIEN LAKI â LAKI DAN PEREMPUAN DI RSGM PROF. SOEDOMO TAHUN 2008 -2013 - , DAVID SUGIHARTANA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Age estimation has significant roles in the health scope, in dentistry it can be used to support the diagnoses, treatment plans, along with the prognoses of dental treatments. The Olze method for the third molar eruption is the simplest method to observe the age estimation. The aims of the study was to compare chronological age between male and female patients of Prof. Soedomo Dental and Oral Health Hospital based on Olze et alâs mandibular third molar eruption status. Panoramic radiographs of Prof. Soedomo Dental and Oral Health Hospital were chosen pursuant to the exclusion and inclusion criterions, in this way was obtained 188 radiographs consisted of 56 males and 132 females. The age when the radiographs were taken had been recorded. The subjectâs third molar eruption status was classified to four stages according to Olze. Each stage of male and female eruption status was analyzed using t-test and Mann-Whitney U test. All the analysis results from each Olzeâs eruption stage showed no significant difference (P>0.05). It was concluded that the chronological age based on third molar eruption has no significant difference between male and female patients of Prof. Soedomo Dental and Oral Health Hospital .